Pre-clinical models of small cell lung cancer and the validation of therapeutic targets. (3rd March 2020) - Sui, Jane S. Y.; Martin, Petra; Gray, Steven G.
ABSTRACT: Introduction : Small-cell lung cancer (SCLC) is an aggressive form of lung cancer that has a dismal prognosis. One of the factors hindering therapeutic developments for SCLC is that most SCLC is not surgically resected resulting in a paucity of material for analysis. To address this, significant efforts have been made by investigators to develop pre-clinical models of SCLC allowing for downstream target identification in this difficult to treat cancer. Areas covered : In this review, we describe the current pre-clinical models that have been developed to interrogate SCLC, and outline the benefits and limitations associated with each. Using examples we show how each has been used to (i) improve our knowledge of this intractable cancer, and (ii) identify and validate potential therapeutic targets that (iii) are currently under development and testing within the clinic. Expert opinion : The large numbers of preclinical models that have been developed have dramatically improved the ways in which we can examine SCLC and test therapeutic targets/interventions. The newer models are rapidly providing novel avenues for the design and testing of new therapeutics. Despite this many of these models have inherent flaws that limit the possibility of their use for individualized therapy decision-making for SCLC.